In Defense of Four Principles Approach in Medical Ethics - S Dabbagh (Tehran University of Medical Sciences, 2008)
Principlism, in general and Four Principles Approach in particular is largely discussed in current medical ethics. According to principlism, the ethical relationship between physician and patient has to be categorized based on some principles, the principles which are general, action-guiding and could help both the patient and the physician to arrange their ethical behavior. Four Principles Approach which is a principlistic view, has formulated the principles which have to be considered in medical ethics in the light of Rossian ethical framework as follows: respect for autonomy, nonmaleficience, beneficence and justice. Ethical Particularism, on the other hand, strongly criticizes principlism and repudiates the very idea of generalizability in the realm of ethics. According to particularists, the way in which a morally relevant feature like fidelity and justice behave in different ethical occasions is fully context-dependent so that they cannot be patternable in advance. It follows from this that fidelity, for instance, is not a good-making feature, generally speaking. In this paper, firstly, the Rossian ethics is discussed in order to make Four Principles Approach intelligible. Secondly, the main particularists' argument against principlism is formulated. Finally, Particularists' argument is evaluated and its plausibility is discussed.